GEOMETRICAL INTERPRETATION OF AN ANALYTIC HP-TRANSFORMATIONS IN ALMOST KAEHLERIAN SPACES - NEGI, U. S. (International Journal of Mathematical Archive, 2018)
In this paper, we have defined and studied on geometrical interpretation of an analytic holomorphically projective transformations in almost Kaehlerian spaces and several theorems have been obtained.